Effect of saline corrosion environment on fatigue crack growth of 7475-T7351 aluminum alloy under TWIST flight loading. (June 2015) - Chemin, A.E.A.; Saconi, F.; Bose Filho, W.W.; Spinelli, D.; Ruchert, C.O.F.T.
Highlights: We study the corrosion fatigue crack growth under TWIST flight. The analyzes realized permitted to evaluated the corrosion behavior for 7475 T7351 aluminum alloy. It was purpose a schematic illustration which describes the phenomenon observed by authors. It was used Scanning Electron Microscope for precipitated analysis on fracture. Abstract: The corrosion fatigue crack propagation was studied on the 7475 T7351 aluminum alloy under a standardized load sequence for flight simulation tests on transport aircraft wing structures (TWIST) simulated loading under a mean stress 80 MPa. The corrosive environment in tests was salt spray containing 3.5% and 5.0% NaCl. The results indicated that the specimens tested in salt spray fractured after more flights than the samples tested in air, while the crack propagation rates in corrosion environment showed retardation and acceleration. The microfractures in specimens revealed impressions caused by salt crystals and oxides, which may have slowed the propagation rate, competing with the plastic zone resulting from the loading of the flight.